PERBANDINGAN MEDIA ALAT BANTU BATTING TEE DAN HIT AWAY TERHADAP HASIL MEMUKUL BOLA DALAM PERMAINAN SOFTBALL - SUGILAR, HANIF RAKHMAN (2015)
The purpose of this research is to know the effects of media tools of learning are batting tee and hit away of the hit in softball game. The method that used in this research is experiment method. The sampling technique using sampling techniques saturated. Instrument in this research is use productivity test using test fungo hitting batting. The hypothesis in this study, the first is a significant influence of learning using media tools hitting the batting tee to hit results in a softball game, there is an increase of 21.38% and proved to be significantly. The second is that there are significant influences of learning hit using media tools against a hit away the results hit in the game of softball, there is an increase of 5.59 % but not proved significantly. The third is there is a difference significant influence of learning hit uses the media the tools batting the tee and hit away of the results of the hit in the game of softball, an increase in the results of the group batting 21,38 % the tee and hit away 5.59 % will but not there is a difference significant influence between the batting the tee and hit away.